AVALIAÇÃO DO DESENVOLVIMENTO NEUROPSICOMOTOR EM CRIANÇAS QUE FREQUENTAM AS ESCOLAS INFANTIS DE IJUÍ/RS - Maurer, Bruna D. P.; Rosa, Larissa F. d.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo